Giant adrenal myelolipoma - clinical spectrum and management: a single centre experience - Kumar, Santosh; Mittal, Ankur; Sharma, Aditya Prakash; Mukhopadhyay, Abhinandan (International Journal of Research in Medical Sciences, 2016)
Background: Adrenal myelolipomas are rare benign tumor composed of mature adipocytes and normal haematopoetic cells. Giant adrenal myelolipomas are rare clinical entities. Most of them are symptomatic. We present 15 such cases, their clinical spectrum and management. Methods: Retrospective analysis of giant adrenal myelolipomas from a tertiary level institute. Initial diagnosis was made by computed tomography. Results: Mean age of patient was 45.6±11 years with slightly higher female preponderance. All patients were overweight with predominantly left sided adrenal myelolipoma. Majority of them (93%) were symptomatic and presented with abdominal pain, anemia or fever. Mean size of the mass on imaging was 14 cm±6 cm, with largest lesion measuring 26 cm. Conclusions: The article highlights the varying clinical presentations including rare emergency presentations of giant adrenal myelolipomas. A brief literature review is also presented.